Concurrent de novo MACF1 mutation and inherited 16p13.11 microduplication in a preterm newborn with hypotonia, joint hyperlaxity and multiple congenital malformations: a case report - Lanlan Mi; Ruen Yao; Weiwei Guo; Jian Wang; Guoqing Zhang; Xiuxia Ye (BMC, 2024)
Abstract Background The MACF1 gene, found on chromosome 1p34.3, is vital for controlling cytoskeleton dynamics, cell movement, growth, and differentiation. It consists of 101 exons, spanning over 270 kb. The 16p13.11 microduplication syndrome results from the duplication of 16p13.11 chromosome copies and is associated with various neurodevelopmental and physiological abnormalities. Both MACF1 and 16p13.11 microduplication have significant impacts on neural development, potentially leading to nerve damage or neurological diseases. This study presents a unique case of a patient simultaneously experiencing a de novo MACF1 mutation and a hereditary 16p13.11 microduplication, which has not been reported previously. Case presentation In this report, we describe a Chinese preterm newborn girl exhibiting the typical characteristics of 16.13.11 microduplication syndrome. These features include developmental delay, respiratory issues, feeding problems, muscle weakness, excessive joint movement, and multiple congenital abnormalities. Through whole-exome sequencing, we identified a disease-causing mutation in the MACF1 gene (c.15266T > C / p. Met5089Thr). Additionally, after microarray analysis, we confirmed the presence of a 16p13.11 microduplication (chr16:14,916,289 − 16,315,688), which was inherited from the mother. Conclusions The patient's clinical presentation, marked by muscle weakness and multiple birth defects, may be attributed to both the de novo MACF1 mutation and the 16p13.11 duplication, which could have further amplified her severe symptoms. Genetic testing for individuals with complex clinical manifestations can offer valuable insights for diagnosis and serve as a reference for genetic counseling for both patients and their families.